Assessment of Obstructive Sleep Apnea severity: Comparison of the Charlson Comorbidity Index and the Functional Comorbidity Index - Ben Hmida, Lenda; Moussa, Ines; Ayedi, Yosr; Mrassi, Hana; Jallouli, Nour Lahbib; Sahnoun , Imen; Douik El Gharbi, Leila (Psychosomatic Medicine and General Practice, 2025)
Background: Obstructive sleep apnea (OSA) is linked with several comorbidities. Various tools, including the Charlson Comorbidity Index (CCI) and the Functional Comorbidity Index (FCI), are used to assess the influence of comorbidities on the outcomes of chronic diseases. We aimed to compare the predictive ability of the CCI and FCI in assessing how common comorbidities impact the severity of OSA. Methods: A retrospective study was conducted in a Pneumology Department. Data were collected from medical records of patients diagnosed with OSA. OSA severity was defined by an apnea hypopnea index (AHI) >= 30/h and/or a severe excessive daytime sleepiness. The CCI and the FCI were calculated, correlated to OSA severity predictors and compared. Results: Severe OSA was noted in 50.6% of patients and severe excessive daytime sleepiness in 17% of patients. The mean CCI was 0.7 ± 0.9, and the mean FCI was 1.6 ± 0.9. The CCI was statistically and weakly correlated to the AHI (r=0.135; p<0.001) and the Epworth sleepiness scale (r=0.071; p=0.039). The FCI was statistically and weakly correlated to the AHI (r=0.131; p<0.001) and strongly correlated to the Epworth sleepiness scale (r=0.84; p=0.014). For both CCI and FCI, the AUC suggested a model with poor discriminatory ability, not very useful for making predictions of severe OSA, without a statistically significant difference between the two models. Conclusion: The CCI and FCI were statistically and overall, weakly correlated to OSA severity predictors, without a superiority of one index to another in predicting severe OSA or excessive daytime sleepiness.